Pengaruh Experiential Learning terhadap Critical Thinking Skill Siswa SMA pada Mata Pelajaran Geografi - Baiq Irnawati; Syafril Syafril; Nurin Rochayati; Mas'ad Mas'ad; Siti Sanisah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to explore the influence of the Experiential Learning model on critical thinking among high school students in Geography lessons. Essentially, this study focuses on the urgent need to develop higher-level critical thinking among students, which has not been optimized due to traditional teaching methods. This study employs a quantitative approach with a quasi-experimental design, involving two classes: one as the experimental class following experiential learning-based instruction, and the other as the control class using conventional teaching methods. The research was conducted at SMAN 1 Pujut High School, with a sample of two classes: IPS 1 and IPS 2. Data collection techniques included observation, documentation, and evaluation tests. For data analysis, descriptive statistics (mean, standard deviation) and inferential statistics, including t-tests and simple linear regression, were used. The research findings indicate a significant difference between the critical thinking abilities of students in the experimental class and the control class. The average posttest scores of students in the experimental class were higher (M = 73.426; SD = 7.873) than those in the control class (M = 77.191; SD = 9.329). The t-test showed a significant p-value of p < 0.05. Therefore, it can be concluded that the use of experiential learning is effective in improving students' critical thinking in geography learning at the high school level. Students develop critical thinking skills through learning experiences. In addition to improving critical thinking skills, students are also motivated to learn. Variations in learning models such as this will improve the quality of education.